American Indian Poverty in the Contemporary United States. Issue 1 (7th December 2015) - Davis, James J.; Roscigno, Vincent J.; Wilson, George
Abstract : Little sociological attention over the last two decades has focused on the deprivation experienced by indigenous people. Fusing insights from American Indian history and the race and labor market inequality literatures, we address this gap in this article through a historically informed labor market analysis of poverty—an analysis that considers the pervasiveness of contemporary Native poverty, its potential basis in labor market opportunities, and the extent to which it has been patterned by two major demographic and economic shifts: (1) the rapid urbanization of the American Indian population and (2) the proliferation of tribally owned casinos. Findings reveal, most notably, the incredibly rigid and durable character of poverty for this population, historically and currently and across geographic space, and with little overall impact of local labor market opportunity. The presence of tribal casinos reduces such poverty, but only to a small degree and not nearly enough to compensate for sizable American Indian and white poverty differentials. Group history is key, we conclude, to shaping how space, labor markets, and economic development reduce or buttress relations of inequality.